2008
DOI: 10.1007/s10266-008-0081-4
|View full text |Cite
|
Sign up to set email alerts
|

Measurement accuracy and perceived quality of imaging systems for the evaluation of periodontal structures

Abstract: The aim of this study was to compare the subjective diagnostic quality of F-speed film images and original and enhanced storage phosphor plate (SPP) digital images for the visualization of periodontal ligament space (PLS) and periapical (PB) and alveolar crestal bone (CB) and to assess the accuracy of these image modalities for the measurement of alveolar bone levels. Standardized images of six dried mandibles were obtained with film and Digora SPPs. Six evaluators rated the visibility of anatomical structures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 25 publications
0
8
0
1
Order By: Relevance
“…These include application of a brightness and contrast algorithm, allowing observers to adjust brightness and contrast themselves and presetting the brightness and contrast. [17][18][19] In a study by Baksi, the author preset the brightness and contrast himself. 19 This, however, represents only one person's perception of the ideal brightness and contrast.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…These include application of a brightness and contrast algorithm, allowing observers to adjust brightness and contrast themselves and presetting the brightness and contrast. [17][18][19] In a study by Baksi, the author preset the brightness and contrast himself. 19 This, however, represents only one person's perception of the ideal brightness and contrast.…”
Section: Discussionmentioning
confidence: 97%
“…[17][18][19] In a study by Baksi, the author preset the brightness and contrast himself. 19 This, however, represents only one person's perception of the ideal brightness and contrast. Other observers may not have the same preference and thus bias may be introduced.…”
Section: Discussionmentioning
confidence: 97%
“…This finding in according to Eickholz et al (8) that concluded that all the radiographic modalities underestimate the real amount of the bone loss. Baksi also stated that PSP accuracy is comparable with plain film in assessment of periodontal structures (9). Persson showed that panoramic can be used instead of full-mouth periapical in periodontitis patients (10).…”
Section: Discussionmentioning
confidence: 99%
“…A number of methodologies for computerized analysis of digital intra‐oral images have been introduced for the detection of periodontal alveolar bone loss. These include specific image enhancements , densitometric analysis , line density functions or application of digital subtraction radiography techniques .…”
Section: Enabling Imaging Technologiesmentioning
confidence: 99%